An update on the role of testosterone replacement therapy in the management of hypogonadism. (April 2016) - Hackett, Geoffrey
While US testosterone prescriptions have tripled in the last decade with lower trends in Europe, debate continues over the risks, benefits and appropriate use of testosterone replacement therapy (TRT). Some authors blame advertising and the availability of more convenient formulations whilst other have pointed out that the routine testing of men with erectile dysfunction (a significant marker of cardiovascular risk) and those with diabetes would inevitably increase the diagnosis of hypogonadism and lead to an increase in totally appropriate prescribing. They commented that this was merely an appropriate correction of previous underdiagnosis and undertreatment by adherence to evidence-based guidelines. Urologists and primary care physicians are the most frequent initiators of TRT, usually for erectile dysfunction. Benefits are clearly established for sexual function, increase in lean muscle mass and strength, mood and cognitive function, with possible reduction in frailty and osteoporosis. There remains no evidence that TRT is associated with increased risk of prostate cancer or symptomatic benign prostatic hyperplasia, yet the decision to initiate and continue therapy is often decided by urologists. The cardiovascular issues associated with TRT have been clarified by recent studies showing clearly that therapy associated with clear rise in testosterone levels are associated with reduced mortality. Studies reporting to show increased risk have been subject to flawed designs with inadequate baseline diagnosis and follow-up testing. Effectively they have compared nontreated patients with undertreated or on-compliant subjects involving a range of different therapy regimens. Recent evidence suggests long acting injections may be associated with decreased cardiovascular risk but the transdermal route may be associated with potentially relatively greater risk because of conversion to dihydrotestosterone by the effect of 5α reductase in skin. The multiple effects of TRT may add up to a considerable benefit to the patient that might be underestimated by the physician primarily concerned with his own specialty. This paper will attempt to identify who should be treated, and how they should be treated safely to achieve best outcomes, based on a comprehensive MEDLINE and EMBASE and Cochrane searches on hypogonadism, TRT and cardiovascular safety from May 2005 to May 2015. This revealed 1714 papers with 52 clinical trials and 32 placebo-controlled randomized, controlled trials.